Resting behavior of broilers reared with or without artificial brooders - Forslind, Sara; Hernandez, Carlos E.; Riber, Anja B.; Wall, Helena; Blokhuis, Harry J. (Frontiers in Veterinary Science, 2022)
Rest and sleep are important for the welfare of mammals and birds. A large part of the daily time budget of broiler chickens is taken up by resting behaviour and the quality of resting is important. However, in intensive broiler production systems, disruptions of resting behaviours are common. These disruptions of resting behaviour could be negative for the health and growth of the birds. This study investigated if artificial brooders that provide a delimited and darker resting place, away from active birds, reduce disruptions of resting behaviour compared to a control situation without artificial brooders. Six pens of each treatment were used in the same building, keeping 60 chickens (Ross 308) per pen. The artificial brooders were removed at 21 days of age. Data on disturbances and duration of resting bouts and activity between resting bouts were collected on 20 and 34 days of age. Also, as an indicator of the quality of rest, the animals´ cognitive performance was evaluated in a spatial learning test that was performed at 11 days of age. The results showed that birds housed in pens with access to brooders have longer resting bouts (260.7 ± 5.2s vs. 132.8 ± 5.3s, p < 0.001) and are less likely to be disturbed during resting by other individuals (0.15 vs. 0.48, p < 0.001). The effect of the artificial brooders on both the duration of resting bouts and the proportion of disturbances remained after the removal of the brooders at 21 days of age. The duration of activity between resting bouts was shorter if the resting bout was ended by a disturbance (9.98 ± 1.0s vs. 61.0 ± 2.4s, p < 0.001). Birds reared with brooders were more likely to solve the spatial learning task (0.5 vs. 0.27, p < 0.01), but those succeeding were not faster at solving it. Broilers may be exposed to disrupted rest due to the lack of a dedicated resting place separated from areas with high activity. Using artificial brooders reduces disturbances but do not eliminate them. Therefore, additional changes to the housing conditions or management will be needed to prevent disturbances.